Time-dependent behaviours of railway prestressed concrete sleepers in a track system. (September 2021) - Li, Dan; Kaewunruen, Sakdirat; You, Ruilin
Highlights: Nonlinear FEM of a prestressed concrete sleeper is presented. Field measurements are used for validations of the time-dependent simulations. Creep and shrinkage properties are taken fully into account. It is the first time that the time-dependent effects are considered throughout the models. Flexural stress resultants of the prestressed concrete sleepers are underestimated by design. Abstract: The main functions of railway sleepers are: (i) to safely transfer loads from wheel axles to foundation; (ii) to secure both rails ensuring correct track gauge at all time; and, (iii) to restrain movements of rails to control longitudinal creeps. In reality, railway industry can experience costly problems of railseat twists and tight gauges, for instance, due to time-dependent actions and poor workmanship. These problems prevent trains to navigate over tracks safely, effectively and quietly. They require additional, expensive maintenance activities much more frequently over time such as rail renewal, rail reprofiling/grinding, rail pad replacement, curve lubrication adjustment, etc. On this ground, it is very important to maintain the geometry and topological/dimensional stability of railway sleepers. The long-term geometric performance of sleepers can be significantly influenced by time-dependent actions and behaviours. The creep and shrinkage in prestressed concrete sleepers result in internal actions that is led to geometric deformation, which change the rail gauge and influence the safety and reliability of track components. Time-dependent behaviours also lead to increased complex internal stresses, which can cause cracking on prestressed concrete railway sleepers. The cracks stemming from creep and shrinkage can be observed in real life, at a certain time after construction, along the sleepers and near the fasteners such as anchorage, bolt holes, and web openings. In this study, unprecedented experimental and numerical investigations are conducted to evaluate time-dependent behaviours of full-scale prestressed concrete sleepers. An empirical calculation method is also introduced and the empirical results are compared with both experimental and numerical results. Insights into creep and shrinkage effects are highlighted in order to essentially aid predictive and preventative track maintenance, supporting the effective and efficient decision making of both (i) engineers and manufacturers and (ii) infrastructure managers and owners.